Quality of educational evaluation in Algerian secondary schools - an analytical study of the baccalaureate exam in the subject of natural sciences, specialization in experimental sciences, in light of the theory of multiple intelligences - maamouri, ameur; djafer , sabah (Journal of Social Sciences and Humanities, 2024)
The present research aims to reveal to what extent the content of the questions of the baccalaureate in natural sciences includes multiple types of intelligences. The researchers adopted the descriptive analytical approach to determine the extent of this objective, using the content analysis method as one of them. methods of the descriptive approach and construct a form of analysis for the types of multiple intelligences by reviewing the literature and previous studies. Check the validity of the tool by presenting it to a group of referees, in addition to the face validity after applying the Cooper. equation, to obtain a validity equal to 0.83, which makes which means that the tool has an acceptable level of validity, as for reliability, it was obtained in two ways: an agreement between two analysts with a result equal to 0.81, and consistency over time using the Cooper's equation to obtain a result of 0.85, which means that the analysis form has an acceptable level of reliability. After using frequencies and percentages to reveal the availability of models and indicators of multiple intelligences, the results were as follows: The questions of the baccalaureate examination in natural and life sciences for the third year of secondary education, specialization in experimental sciences, obtained 341 distributed frequencies. out of nine intelligences, natural intelligence having obtained the highest frequency of its indicators, estimated with a rate of 67.67%, followed by logical-mathematical intelligence with a rate of 57.27% and subjective intelligence personal with a rate of 57.27%and personal subjective intelligence comes next with a rate of 59.59%, then it is followed by verbal-linguistic intelligence, where the frequency of its indicators reaches 55.45%, then it is followed by by visual-spatial intelligence with a rate of 46.59%, then bodily-kinesthetic intelligence with a rate of 42.04%, then it is followed by existential intelligence with a rate of 03.40%, and it arrived Existential intelligence was followed by 0.17%, and musical intelligence had the lowest percentage of frequency its indicators were estimated at 01.13%, and the percentage of inclusion of multiple intelligences in the content of the book studied was estimated at 39.74%, which is a percentage considered low compared to the spoken percentage, which experts set at 70%. We see that the content of the test document studied does not neglect any of the nine intelligences, but these are distributed in varying proportions, the distribution being natural intelligence in the content of the studied test has a high percentage, because the orientation of questions and activities is a natural environmental orientation, taking into account the specialization of the division, and therefore its lack of interest in subjects which develop both existential. and musical intelligence appeared.